Influence before and after Early Mobilization of Changes in Pain Levels in Post Orthopedic Surgery Patients at Royal Prima Medan Hospital in 2021 - Zhan Chengwu; Florenly; Johannes Bastira Ginting; Fioni (Britain International for Academic Research (BIAR) Publisher, 2022)
Orthopedic surgery is a surgical action associated with the correction of musculoskeletal system deformities and orthopedic problems that aim to improve function by restoring movement and stability and reducing pain and disabilities. Early mobilization is a prominent factor in speeding up postoperative recovery and may prevent postoperative complications. This study aims to find out the influence before and after early mobilization of changes in pain levels in orthopedic postoperative clients at RSU Royal Prima. This type of research uses a correlational descriptive research design, using the One Group Pretest-Postest approach. The location of this study was conducted at RSU Royal Prima Medan in March 2021. The population of all patients’ post-surgery orthopedic hospitalization amounted to 176 patients. The size of the sample uses the formula Structural Equation Modelling (SEM), then the number of samples is determined to be 100 people. Univariate analysis, bivariate with t-dependent test (paired t-test) with a meaningful limit of 0.05. The results of the study that there was a change in the level of pain Wilcoxon test results at the time of the pre-test the result of the mean value of 3.82, at the time of the post-test test the mean value was 2.34. So the result of Z = -5,358 then p-value as much as 0.004 < 0.05 so that Ho is rejected and Ha accepts. The conclusion of the level of pain before early mobilization in the client post orthopedic surgery the majority feels even more pain and the minority experience severe pain. The level of pain after early mobilization in the majority of orthopedic postoperative clients was slightly more painful and the minority felt even more pain. There is an early mobilization effect on pain changes in orthopedic postoperative clients in patients in the hospital room of RSU Royal Prima in 2021.